Shaping Purchase Intentions: The Impact of Perceived Usefulness, Ease of Use, and Compatibility on Attitudes Toward Behaviour - Rahardjo, Kusdi; Afrianty, Tri Wulida; Prakasa, Yudha (FIA UB, 2026)
The increasing recognition of the potential consequences of environmental degradation has heightened public awareness regarding the significance of sustainability. One notable source of ecological pollution arises from motor vehicles' release of air pollutants. This investigation aims to explore the impact of Attitude Toward Behaviour on Purchase Intention by examining the determinants that influence the adoption of Attitude Toward Behaviour. Four hundred thirty-six online drivers from the Greater Malang area in Indonesia participated in the study using a survey approach. Structural equation modelling, utilising PLS-SEM, was employed for data analysis. The research findings indicate that both Perceived Usefulness and Perceived Ease of Use significantly affect Attitude Toward Behaviour, and Attitude Toward Behaviour, in turn, substantially influences Purchase Intention. These findings could offer valuable insights for online drivers aiming to enhance their inclination towards adopting electric vehicles.